Identifying critical success factors for the implementation of enterprise resource planning systems in public educational institutions - Campos Fernandes Leandro, Flávia; Picinini Méxas, Mirian; Meirelles Drumond, Geisa (Brazilian Journal of Operations & Production Management, 2017)
The implementation of Enterprise Resource Planning (ERP) systems in Brazilian public educational institutions is considered critical and a time consuming process. Then this study aims to identify the Critical Success Factors (CSF) for the implementation of ERP systems in these organizations. A literature review, where 30 CSF used in scientific articles were identified, has been prepared. Based on found CSF, 20 were selected to compose a questionnaire constructed with the Likert scale and applied to 70 ERP systems specialists in educational institutions, in order to get the perception of the most CFS relevant during the pre-implementation, implementation and post-implementation phases. As a result of this field survey, a ranking of the degree classification "very important" for 20 CFS was drafted by percentage in the ERP lifecycle. This work intends to contribute with a comprehension in terms of what CFS needs to be observed during each phase of the ERP systems implementation in educational institutions.